Linguistic Peculiarities of the Name of Diseases in the Vocabulary and Text Interpretation - Ergashova Shokhida Ulmasovna (Genius Publishing Group, 2022)
This article is devoted to the study of the linguistic features of the names of diseases in dictionary and textual interpretation, as well as the consideration of these points in the materials of the Russian and English languages.
Keywords: Linguistics; name of diseases; dictionary and test interpretation; lexical-thematic group; semantics; nomination